Challenging the “Half-Hearted” Fulfillment of the Rights of Workers with Disabilities - Abrianto, Bagus Oktafian; Tinambunan, Hezron Sabar Rotua (Disable, 2025)
This study finds that there is a persistent legal conflict and regulatory disharmony between national provisions on disability employment quotas and their implementation at the company level. Empirical evidence shows that many companies fail to meet the quota obligation due to the absence of qualified applicants with disabilities, unprepared workplace environments, and the lack of operational technical guidelines. Furthermore, the absence of explicit sanctions in existing regulations creates legal uncertainty and weakens enforcement. Using a normative legal method with a statute and conceptual approach, this research analyzes the relevant legal framework and constructs arguments based on legal principles and theories in labor law concerning the rights of persons with disabilities. The study reveals that the current regulatory framework lacks integrated monitoring mechanisms, measurable evaluation indicators, and clear administrative sanctions, while also failing to provide incentives that could encourage compliance. The novelty of this research lies in offering a combined legal and policy framework that bridges the gap between normative provisions and practical implementation, supported by recommendations for detailed technical guidelines, accessibility audits, and structured incentive schemes. These findings contribute to strengthening inclusive labor policies in Indonesia, ensuring that the principle of inclusivity becomes a measurable and enforceable standard rather than a rhetorical aspiration.